Sexual Transmission of XMRV: A Potential Infection Route - Prachi Sharma; Kenneth A. Rogers; Suganthi Suppiah; Ross J. Molinaro; Nattawat Onlamoon; John Hackett; Gerald Schochetman; Eric A. Klein; Robert H. Silverman; François Villinger (Advances in Virology)
Although XMRV dissemination in humans is a matter of debate, the prostate of select patients seem to harbor XMRV, which raises questions about its potential route of transmission. We established a model of infection in rhesus macaques inoculated with XMRV. In spite of the intravenous inoculation, all infected macaques exhibited readily detectable XMRV signal in the reproductive tract of all 4 males and 1 female during both acute and chronic infection stages. XMRV showed explosive growth in the acini of prostate during acute but not chronic infection. In seminal vesicles, epididymis, and testes, XMRV protein production was detected throughout infection in interstitial or epithelial cells. In the female monkey, epithelial cells in the cervix and vagina were also positive for XMRV gag. The ready detection of XMRV in the reproductive tract of male and female macaques infected intravenously suggests the potential for sexual transmission for XMRV.